Motor learning by cross education in Hemi-Parkinson: a neuroimaging feasibility study of the effects of virtual mirrored sensory feedback - Ori, Ossmy; Lihi, Mansano; Silvi, Frenkel-Toledo; Evgeny, Kagan; Shiri, Koren; Roee, Gilron; Daniel, Reznik; Nachum, Soroker; Roy, Mukamel (International Conference on Virtual Rehabilitation (Print), 2019)
Cross education is a phenomenon in which motor training of one hand induces motor learning in the other hand. We have recently shown in healthy subjects that the effect of cross-education is significantly augmented by provision of real-time manipulated bi-modal (visual and kinesthetic) sensory feedback, creating an illusory sensation of voluntary training with the other hand. Here we tested whether this training method may be applicable also in pathological conditions affecting one side of the body. We present here data showing behavioral gain accompanied by changes in functional magnetic resonance imaging dynamics following training with this setup in the case of patient LA, a young man with significant unilateral upper-limb dysfunction stemming from hemi-Parkinson's disease. Following two weeks of daily sessions in which he intensively trained the non-affected upper limb, he showed improvement in motor capacity of the affected limb, accompanied by enhanced activation in the pre-frontal cortex and a widespread increase in functional coupling in the brain. Results from the current feasibility study suggest that combining cross-education with manipulated sensory input may have beneficial effects in clinical conditions.